Exploring Teenagers’ Motivation to Continue Their Education and the Dynamics of Influencing Factors - Naimah Putri Atdika; Sesilia Pamela; Muhammad Rizki; Rika Fitri Ramadani (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to explore adolescents' enthusiasm in continuing their education and understand the dynamics of factors influencing it. In social life, adolescents have various considerations in determining their educational pathways after completing school. This research employed a qualitative approach using a case study method. Data were collected through observation and interviews with several informants. The findings show that adolescents’ enthusiasm in continuing education is influenced by various factors such as economic conditions, perceptions of education, and social environment. These factors not only present challenges but also shape adolescents' perspectives and decisions regarding their future. Therefore, creative, flexible, and needs-based approaches in community education are needed to support and strengthen adolescents' enthusiasm for continuing education.